Perilaku Komunikasi Anggota Komisi IV DPR RI dalam Rapat Dengar Pendapat dengan Kementerian Pertanian tahun 2010 - H Harahap; S.S. Agung; B. Ginting; D.S. Gani (Institut Pertanian Bogor, 2012)
Abstract One function of Parliament is to defend the interests of the people in any government program. Function is reflected in the communication behavior of members of Parliament in the event of a hearing. This study aims to describe the communication behavior of members of the Komisi IV DPR RI in a hearing with the Ministry of Agriculture 2010. Communication behavior is observed from the content of the communication messages that include: contents of interests, substance, orientation, type of reason, evidence, clarity, accommodative, and speak act. This study uses content analysis methods and all hearing documents used as research material. The study result (66.1%) a message containing the public interest, the messages (80.1%) according to the substance of the meeting, orientation (42.1%) solution of the problem, type reasons (62.2%) using a factual, a form of evidence (45 , 5%) narrative, willingness to accept (65.1%) accommodative, sentences (89.9%) are clear and type speak act (51.9%) using assertive. Keywords: message contents, strategy, hearing.